Efficient additive for pyrometallurgical steel dust and sludge and application process of efficient additive

By using high-efficiency additives made of silicon calcium slag, carbon fiber, polycarbonsilane and polyvinyl alcohol in the ignition smelting steel dust sludge process, the problems of low iron metallization and dezincification are solved, and more efficient resources are achieved Utilization and quality improvement of finished products.

CN119464705AInactive Publication Date: 2025-02-18中科博一环保科技有限公司 +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510076233.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing ignition smelting steel dust sludge process, the iron metallization rate and dezincification rate are relatively low, which affects its utilization value.

Method used

Using a highly efficient additive made of silicon calcium slag, carbon fiber, polycarbosilane and polyvinyl alcohol, it is used to coat the core material to form a film layer to improve its efficiency in ignition smelting.

Benefits of technology

It significantly improves the iron metallization rate and dezincification rate of steel dust sludge, enhances the resource utilization value of the finished product, and avoids the oxidation and aggregation of core materials during storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an efficient additive for pyrometallurgy of steel dust and sludge and an application process thereof, and belongs to the technical field of metal smelting, the efficient additive provided by the invention comprises an inner core material and a shell, the inner core material comprises the following raw materials in parts by mass: 35-55 parts of silicon-calcium slag, 10-30 parts of carbon fiber, 5-12 parts of lignite and 1-8 parts of polycarbosilane; and the shell is a film layer prepared from polyvinyl alcohol. The additive and the steel dust and sludge are mixed, granulated and then subjected to reduction roasting, and reduction of metal oxides in the steel dust and sludge is achieved. The carbon fiber and the lignite in the additive can be used as a reducing agent, the silicon-calcium slag can be used as a carbon dioxide adsorbent, the polycarbosilane is used as a binder, hydrogen and silicon carbide generated by pyrolysis can promote a reduction reaction, and humic acid in the lignite has adsorption and binding effects and is beneficial to raw material mixing and granulation. By adding the efficient additive provided by the invention into the pyrometallurgy steel dust and sludge, the steel dust and sludge can be efficiently dezincified, and the metallization ratio of iron is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal smelting, and in particular relates to a high-efficiency additive for pyrometallurgical steel dust and mud and an application process thereof. Background Art

[0002] Steel dust sludge originates in steel production workshops and generally refers to waste generated by dust removal equipment used to remove high-temperature flue gases during processes such as raw material processing, sintering, pelletizing, ironmaking, and steelmaking. It also refers to waste generated during subsequent processing and cleaning. Steel dust sludge has four characteristics: diverse sources and high production volume; complex composition, low content, and high volatility; small particle size, posing a significant risk of pollution; and high potential for resource utilization.

[0003] Steel dust sludge treatment processes are categorized into physical, wet, and pyrometallurgical methods. Physical methods offer advantages such as simplicity and low investment costs, but they are inefficient and are typically used only as pretreatment for both pyrometallurgical and wet processes. Wet treatment processes include acid leaching, alkaline leaching, and ammonia leaching. Wet treatment processes offer high leaching rates and can selectively recover zinc and iron, but they typically consume large amounts of leaching agents, generate significant amounts of wastewater, and corrode equipment. Representative pyrometallurgical treatment processes include the rotary kiln, rotary hearth furnace, and oxygen-enriched hot blast shaft furnace (OxyCup) processes. These processes effectively utilize iron, carbon, and CaO in steel metallurgical dust sludge while recovering high-value-added resources such as zinc oxide powder. They are the primary treatment methods used by steel companies for secondary resource utilization. However, the iron metallization rate of the pellets currently produced after treatment is only 70-80%, and the zinc content exceeds 0.5%, severely limiting their value. Therefore, improving the metallization rate and zinc removal rate of treated steel dust sludge products is an urgent issue. Summary of the Invention

[0004] The object of the present invention is to provide a high-efficiency additive for pyrometallurgical steel dust and its application process, so as to improve the iron metallization rate and dezincification rate of pyrometallurgical steel dust.

[0005] The purpose of the present invention can be achieved through the following technical solutions: The present invention provides a high-efficiency additive for pyrometallurgical steel dust and mud, the high-efficiency additive comprising a core material and an outer shell; The core material is a spherical particle prepared from a mixture of calcium silicate slag, carbon fiber and polycarbosilane; the raw materials of the core material include 35-55 parts of calcium silicate slag, 10-30 parts of carbon fiber, 5-12 parts of lignite and 1-8 parts of polycarbosilane by mass; The shell is a film layer prepared from polyvinyl alcohol.

[0006] Furthermore, the alcoholysis degree of the polyvinyl alcohol is 70%-80%.

[0007] Furthermore, the diameter of the carbon fiber is 50-200 nm.

[0008] Furthermore, the calcium oxide content in the calcium-silicon slag is 40-60 wt%.

[0009] Furthermore, the thickness of the shell is 10-30 μm, and the particle size of the core material is 1-3 mm; Furthermore, the preparation steps of the high-efficiency additive are as follows: Step 1: dry-milling the calcium silicon slag and lignite and sieving them through a 1000 mesh screen. The sieved calcium silicon slag, lignite, carbon fiber and polycarbosilane are put into a blender for stirring. Water is added according to a solid-liquid mass ratio of 10:1, and the mixture is granulated to obtain a core material. Step 2: dissolving polyvinyl alcohol in water to form a 20 wt% polyvinyl alcohol solution; Step 3: Place the core material in a vacuum drying oven at 50°C and dry for 12 hours, then take it out and spray the polyvinyl alcohol solution in the form of mist on the surface of the dried core material. After vacuum drying at 60°C for 3 hours, a film layer is formed to obtain a high-efficiency additive.

[0010] The present invention also provides an application process of the above-mentioned high-efficiency additive for pyrometallurgical steel dust and mud, the application process comprising the following steps: Step 1: Add the high-efficiency additive into water and stir to mix, with a solid-liquid mass ratio of 5:1. After the film layer is dissolved, ultrasonic dispersion is performed for 30 minutes to obtain an additive dispersion; Step 2: mixing the steel dust and the additive dispersion in a mass ratio of 10:6 to obtain a mixture; Step 3: Press the mixture into balls to obtain raw balls with a particle size of 5-20 mm, and dry and dehydrate them to a water content of <3 wt%; Step 4: The dried raw material balls are subjected to reduction roasting for 1-2 hours to obtain metallized pellets, which are then cooled to 100°C to obtain the finished product; Step 5: The flue gas generated by the roasting is passed into the oxidation chamber, air is introduced into the oxidation chamber, and then enters the waste heat boiler to recover waste heat. After the temperature is lower than 200°C, it enters the dust collector to collect the smoke and obtain the zinc oxide product.

[0011] Furthermore, the reduction roasting process of the raw material ball includes a preheating stage, a high temperature stage and a discharging stage, wherein the temperature of the preheating stage is 1000-1100°C, the temperature of the high temperature stage is 1200-1300°C, and the temperature of the discharging stage is 900-1000°C.

[0012] Beneficial effects of the present invention: Coating the additive with polyvinyl alcohol can prevent the core material from oxidation and agglomeration during storage, and adding water to dissolve the outer film before application can increase the viscosity of the solution and improve the dispersibility. The prepared raw material balls have uniform composition and strong adhesion between particles.

[0013] During the reduction roasting process of steel dust, lignite and carbon fiber can increase the reducing carbon content in the raw material balls and improve the efficiency of reducing zinc oxide and iron oxide. Polycarbosilane, as a high-temperature binder, has a low melting point and melts at 200°C to form a viscous liquid, which improves the bonding of inorganic materials and produces hydrogen and silicon carbide during high-temperature decomposition, promoting the reduction of zinc oxide and iron oxide. The humic acid contained in lignite has adsorption and bonding effects, which is beneficial to the mixing and granulation of raw materials. The high content of calcium oxide in silica-calcium slag is used as a carbon dioxide adsorbent to promote the reduction reaction involving carbon monoxide, realize the recycling of waste, and improve the metallization rate and dezincification rate of the finished products obtained from pyrometallurgical steel dust. DETAILED DESCRIPTION

[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0015] Example 1 This embodiment provides a high-efficiency additive, including a core material and a shell. The core material is a spherical particle prepared from a mixture of calcium silicate slag, carbon fiber, and polycarbosilane. The raw materials of the core material include 35 parts of calcium silicate slag, 30 parts of carbon fiber, 5 parts of lignite, and 1 part of polycarbosilane by weight. The shell is a film layer prepared from polyvinyl alcohol. The specific preparation steps are as follows: Step 1: dry-milling calcium silicate slag (calcium oxide content of 40-60wt%) and lignite, followed by sieving through a 1000 mesh screen. The sieved calcium silicate slag, lignite, carbon fiber (diameter of 50-200nm) and polycarbosilane are then put into a blender for stirring. Water is added at a solid-liquid mass ratio of 10:1, and the mixture is granulated to obtain a core material (particle size of 1-3mm). Step 2: dissolving polyvinyl alcohol (with a degree of alcoholysis of 70%-80%) in water to form a 20 wt% polyvinyl alcohol solution; Step 3: Place the core material in a vacuum drying oven at 50°C and dry for 12 hours, then take it out and spray the polyvinyl alcohol solution in the form of mist on the surface of the dried core material. After vacuum drying at 60°C for 3 hours, a film layer (thickness of 10-30 μm) is formed to obtain a high-efficiency additive.

[0016] Example 2 The difference from Example 1 is that the raw material ratio of the core material is replaced by: 45 parts of silica-calcium slag, 20 parts of carbon fiber, 5 parts of lignite and 1 part of polycarbosilane, and the other steps and conditions are the same as Example 1.

[0017] Example 3 The difference from Example 1 is that the raw material ratio of the core material is replaced by: 55 parts of silica-calcium slag, 10 parts of carbon fiber, 5 parts of lignite and 1 part of polycarbosilane, and the other steps and conditions are the same as Example 1.

[0018] Example 4 The difference from Example 2 is that the raw material ratio of the core material is replaced by: 45 parts of silica-calcium slag, 20 parts of carbon fiber, 5 parts of lignite and 5 parts of polycarbosilane. The other steps and conditions are the same as Example 2.

[0019] Example 5 The difference from Example 2 is that the raw material ratio of the core material is replaced by: 45 parts of silica-calcium slag, 20 parts of carbon fiber, 5 parts of lignite and 8 parts of polycarbosilane. The other steps and conditions are the same as Example 2.

[0020] Example 6 The specific steps of using additives to pyrometallurgical steel dust sludge are as follows: Step 1: Add the additive prepared in Example 1 into water and stir to mix, with a solid-liquid mass ratio of 5:1. After the film layer is dissolved, ultrasonic dispersion is performed for 30 minutes to obtain an additive dispersion; Step 2: mixing the steel dust and the additive dispersion in a mass ratio of 10:6 to obtain a mixture; Step 3: Press the mixture into balls to obtain raw balls with a particle size of 5-20 mm, and dry and dehydrate them to a water content of <3 wt%; Step 4: The dried raw material balls are subjected to reduction roasting. The raw material balls undergo a preheating stage, a high temperature stage, and a discharging stage in sequence. The preheating stage temperature is 1000-1100°C, the high temperature stage temperature is 1200-1300°C, and the discharging stage temperature is 900-1000°C. The raw material balls are roasted for 1-2 hours to obtain metallized pellets, and then cooled to 100°C to obtain the finished product. Step 5: The flue gas generated by the roasting is passed into the oxidation chamber, air is introduced into the oxidation chamber, and then enters the waste heat boiler to recover waste heat. After the temperature is lower than 200°C, it enters the dust collector to collect the smoke and obtain the zinc oxide product.

[0021] Example 7 The difference from Example 6 is that the additive is replaced by the additive prepared in Example 2, and the other steps and conditions are the same as Example 6.

[0022] Example 8 The difference from Example 6 is that the additive is replaced by the additive prepared in Example 3, and the other steps and conditions are the same as Example 6.

[0023] Example 9 The difference from Example 6 is that the additive is replaced by the additive prepared in Example 4, and the other steps and conditions are the same as Example 6.

[0024] Example 10 The difference from Example 6 is that the additive is replaced by the additive prepared in Example 5, and the other steps and conditions are the same as Example 6.

[0025] Comparative Example 1 Compared with Example 6, no additives were added during the pyrometallurgical smelting of steel dust in this comparative example. The specific steps were as follows: Step 1: mixing steel dust and water in a mass ratio of 10:1 to obtain a mixture; Step 2: Press the mixture into balls to obtain raw balls with a particle size of 5-20 mm, and dry and dehydrate them to a water content of <3 wt%; Step 3: The dried raw material balls are subjected to reduction roasting. During the roasting process, the raw material balls sequentially undergo a preheating stage, a high temperature stage, and a discharging stage. The temperature of the preheating stage is 1000-1100°C, the temperature of the high temperature stage is 1200-1300°C, and the temperature of the discharging stage is 900-1000°C. The raw material balls are roasted for 1-2 hours to obtain metallized pellets, which are then cooled to 100°C and discharged to obtain finished products. Step 4: The flue gas generated by the roasting is passed into the oxidation chamber, air is introduced into the oxidation chamber, and then enters the waste heat boiler to recover waste heat. After the temperature is lower than 200°C, it enters the dust collector to collect the smoke and obtain the zinc oxide product.

[0026] The finished products prepared in Examples 6 to 10 and Comparative Example 1 were subjected to performance tests, and the results are shown in Table 1:

[0027] As shown in Table 1, Examples 1-5 prepared additives, while Examples 6-10 used the additives prepared in Examples 1-5 to pyrometallurgically refine steel dust. The ratios of calcium-silicon slag and carbon fiber in the additives used in Examples 6-8 varied, with Example 7 achieving the optimal ratio. The iron metallization rate and zinc removal rate were higher than those in Examples 6 and 8. The additives used in Examples 9 and 10 increased the polycarbosilane content compared to Example 6. This increased polycarbosilane content increased the hydrogen and silicon carbide contents, thereby promoting the reduction reaction and facilitating iron metallization and zinc removal. Comparative Example 1, in which no additives were added to pyrometallurgically refine steel dust, showed significantly higher iron metallization and zinc removal rates in Examples 6-10 than in Comparative Example 1, potentially increasing the resource utilization value of steel dust.

[0028] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0029] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A high-efficiency additive for pyrometallurgical steel dust, characterized in that: The high-efficiency additive comprises a core material and a shell; The core material is a spherical particle prepared from a mixture of calcium silicate slag, lignite, carbon fiber and polycarbosilane; the raw materials of the core material include 35-55 parts of calcium silicate slag, 10-30 parts of carbon fiber, 5-12 parts of lignite and 1-8 parts of polycarbosilane by weight; The shell is a film layer made of polyvinyl alcohol.

2. The high-efficiency additive for pyrometallurgical steel dust and mud according to claim 1, characterized in that: The alcoholysis degree of the polyvinyl alcohol is 70%-80%.

3. The high-efficiency additive for pyrometallurgical steel dust and mud according to claim 1, characterized in that: The diameter of the carbon fiber is 50-200 nm.

4. The high-efficiency additive for pyrometallurgical steel dust and mud according to claim 1, characterized in that: The content of calcium oxide in the calcium-silicon slag is 40-60wt%.

5. The high-efficiency additive for pyrometallurgical steel dust and mud according to claim 1, characterized in that: The thickness of the shell is 10-30 μm, and the particle size of the core material is 1-3 mm.

6. The high-efficiency additive for pyrometallurgical steel dust and mud according to claim 1, characterized in that: The preparation steps of the high-efficiency additive are as follows: Step 1: dry-milling the calcium silicon slag and lignite and sieving them through a 1000 mesh screen, putting the sifted calcium silicon slag, lignite, carbon fiber and polycarbosilane into a mixer for stirring, adding water according to a solid-liquid mass ratio of 10:1, and granulating the mixture to obtain a core material; Step 2, dissolving polyvinyl alcohol in water to form a 20wt% polyvinyl alcohol solution; Step 3: Place the core material in a vacuum drying oven at 50°C and dry for 12 hours, then take it out, spray the polyvinyl alcohol solution in the form of mist on the surface of the dried core material, and form a film layer after vacuum drying at 60°C for 3 hours to obtain a high-efficiency additive.

7. A process for applying a high-efficiency additive to pyrometallurgical steel dust, characterized in that: The high-efficiency additive for treating pyrometallurgical steel dust and mud according to any one of claims 1 to 6 is used, and the application process comprises the following steps: Step 1: Add the high-efficiency additive into water and stir to mix, with a solid-liquid mass ratio of 5:

1. After the film layer is dissolved, ultrasonic dispersion is performed for 30 minutes to obtain an additive dispersion; Step 2, mixing the steel dust and the additive dispersion in a mass ratio of 10:6 to obtain a mixture; Step 3: Press the mixture into balls to obtain raw balls with a particle size of 5-20 mm, and dry and dehydrate them to a water content of <3wt%; Step 4, reducing and roasting the dried raw material balls for 1-2 hours to obtain metallized balls, and cooling to 100° C. to obtain the finished product; Step 5: The flue gas generated by the roasting is passed into the oxidation chamber, air is passed into the oxidation chamber, and then enters the waste heat boiler to recover waste heat. After the temperature is lower than 200° C., it enters the dust collector to collect the smoke and obtain the zinc oxide product.

8. The application process of a high-efficiency additive for pyrometallurgical steel dust and mud according to claim 7, characterized in that: The reduction roasting process of the raw material ball includes a preheating stage, a high temperature stage and a discharging stage, wherein the temperature of the preheating stage is 1000-1100°C, the temperature of the high temperature stage is 1200-1300°C, and the temperature of the discharging stage is 900-1000°C.

Citation Information

Patent Citations

  • Preparation method of a self-fluxing composite pellet

    CN109439896A

  • Sintering process for making cherry small ball by adding water soluble additives in iron concentrate

    CN1114689A

  • Method for reducing and removing zinc and alkali metals from reinforced steel dust and sludge

    CN117248109A

  • Iron ore concentrate powder metallization composite sintering preparation method based on coating pelletizing

    CN118389815A

  • Raw material pellet for reduction-roasting of steel dust, and method of manufacturing the same

    JP2012201947A